Dictionary of similes, idioms, metaphors and proverbs (Pelanduk pocket., 1993)
Perfect for those who believe in getting the message across loud and clear. This fascinating book contains hundreds of english similes, idioms, metaphors and proverbs-the tools for effective communication. It is designed to help the user get his ideas heard and remembered, to generate interest in his listeners and to arouse a favourable response from them.